Human Papillomavirus infection in pregnancy: Clinical and perinatal outcomes in a regional cohort and modern approaches to management - Musayeva, Lala; Aliyeva, Elmira; İsmayilova, Sevinj and Safarova, Saadet and Guliyeva, Sevda (Acta Biomedica Atenei Parmensis, 2026)
Background and Aim: Human papillomavirus (HPV) is among the most common sexually transmitted infections and may be associated with alterations in placental and endocrine function, potentially contributing to adverse pregnancy outcomes. This study aimed to evaluate clinical, hormonal, and perinatal outcomes of HPV-associated genital lesions during pregnancy in Azerbaijan. Methods: A total of 206 pregnant women were examined at Maternity Hospital No. 1 and Antenatal Clinic No. 6 between 2015 and 2022. The study group included 152 women with HPV-associated lesions confirmed by colposcopy, cytology, histology, and polymerase chain reaction (PCR); 54 HPV-negative women served as controls. Clinical, hormonal, microbiological, and instrumental assessments (ultrasound, cardiotocography) were performed. Neonates underwent nasopharyngeal PCR testing 8–12 hours after birth. Results: HPV-positive women had significantly higher rates of threatened miscarriage (28.3% vs 11.1%), anemia (24.3% vs 7.4%), intrauterine infection (18.4% vs 5.6%), and preterm birth (21.1% vs 9.3%) compared with controls. Neonatal complications included low birth weight (19.1% vs 7.4%), intrauterine growth restriction (12.5% vs 3.7%), and reduced Apgar scores (<7 in 15.8% vs 5.6%). Hormonal assays showed decreased β-human chorionic gonadotropin (β-hCG), placental lactogen, and α-fetoprotein (AFP) levels in HPV-positive women. HPV DNA was detected in 32.2% of neonatal nasopharyngeal swabs (49/152), confirming vertical transmission. Conclusions: HPV infection during pregnancy is associated with adverse obstetric and perinatal outcomes and reduced levels of key placental endocrine markers. These findings underscore the importance of early detection, HPV vaccination, and monitoring of placental endocrine function. However, observed hormonal changes should be interpreted as associations rather than confirmed mechanistic effects.